Students Perceptions At An Intermediate Level (CEFR) Of The Use Of Facebook To Practice Writing Skills - Espol (2019)
The aim of this study was to understand how students feel the moment when they are exposed to using the social networking site facebook as a platform for their practicing of writing skills. Writing has been one of the skills that learners have more trouble with, because of several reasons. One of these reasons says carlino (2012) is the lack of proper writing practice during the student’s primary and secondary life. It was this as well as the frustration this author feels when reading some student’s written works that functioned as the motivation to look for a viable tool to help students practice their writing skills. To achieve this goal this research was set into place. the researcher used a survey to secure demographic information as well as facts on how students use the internet and the facebook, which is the platform base of this investigation. Participants additionally did a writing test at the beginning of the intervention and then another test, with the same